POTENSI SCORE 250 EC TERHADAP HASIL PADI VARIETAS IR 64 (Oryza sativa L.) - Erwin Arief Rochyat; Rosid Rosid (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
Improving rice productivity requires proper crop management practices, including effective disease control. The objective of this study is to analyze the potential application of Score 250 EC®, with the active ingredient difenoconazole, for the growth of the IR 64 rice variety (Oryza sativa). The experiment was conducted using a Randomized Block Design (RBD) with seven concentration levels, namely S0 = 0 L (control), S1 = 0.075 L, S2 = 0.150 L, S3 = 0.225 L, S4 = 0.300 L, S5 = 0.375 L, and S6 = 0.450 L, where each concentration was diluted in 500 L of water per hectare (ha⁻¹). The 1,000-grain weight parameter showed a significant effect across treatments compared to the control. The treatment with a concentration of 0.300 L Score per 500 L water ha⁻¹ resulted in the highest average weight of 24.78 g. Meanwhile, for the milled dry grain parameter, the concentration of 0.300 L Score per 500 L water ha⁻¹ produced the highest average yield of 7.21 t ha⁻¹